3163 A Systematic Review of Research Competency Assessments for Clinical Researchers. (27th March 2019) - Ianni, Phillip A; Samuels, Elias M.; Eakin, Brenda; Perorazio, Thomas E
Abstract : OBJECTIVES/SPECIFIC AIMS: The purpose of this study was to summarize the existing literature on clinical research competencies and determine what competency assessments currently exist. We also wished to assess which competencies should be included in a research competency assessment tool and to evaluate the validity of current competency assessments. We also examined whether these competency assessments can be used for the purposes of formative and summative evaluation. METHODS/STUDY POPULATION: Prior to conducting our search of the literature, we first compiled a list of search terms (e.g., clinical, research, training, competencies) that could be used to locate articles. We then entered these search terms, in various combinations, on several relevant databases. We evaluated abstracts of the articles revealed by this search to determine whether they met three criteria. The first criterion was that the subjects of the article must be clinical investigators or clinical investigators in training. Relevant disciplines included medicine, public health, nursing, pharmacy, dentistry, and other related fields. The second criterion was that articles should focus on research-based (as opposed to clinical) skills. The last criterion was that research-based competencies (or related terms like skills, abilities, mastery, knowledge) must be assessed in some way. If the abstract suggested that the article met all three criteria, the full article was retrieved and analyzed in-depth. To identify articles that eluded literature search, we then examined the reference section of these articles and examined articles that cited these articles. When no additional articles could be located, the search for articles stopped. Once a pool of potentially eligible articles was identified, the articles underwent peer review by several researchers experienced with clinical research and competency-based education and assessment. Articles that were unanimously judged to meet the criteria were included in the systematic review. RESULTS/ANTICIPATED RESULTS: Approximately 75 articles were selected and reviewed for eligibility. After peer review, we found that only a small fraction of these articles met our criteria for inclusion in the systematic literature review. Our preliminary findings suggest that there are few assessments of clinical research competency and that many of these assessments are poorly validated. DISCUSSION/SIGNIFICANCE OF IMPACT: The findings of the present study suggest that the validation methods used thus far are limited and so the validity of many of these assessments is effectively unproven. Future research on assessments of clinical research competency ought to address these limitations by sampling clinical researchers, using more rigorous validation methods, and by confirming hypothesized factor structures in new samples. The use of better-validated instruments may enhance measurement of trainees' knowledge and skill levels for the purposes of formative and summative assessment.